STUDENTS’ SYNTACTIC COMPETENCE IN FOCUS TRANSFORMATION SENTENCE - Ida Nuraeni (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2020)
This research aims to describe students' syntactic competence in arranging focus transformation sentence. The researchers employed a qualitative approach of single case study. The data obtained were acceptable sentences from spoken Indonesian language. Meanwhile, the data analysis applied an interactive model. The research result identifies that the Junior High School students, particularly the eighth-graders, has had syntactic competence in arranging focus transformation sentence by practicing the rules of intonation, movement, passive structure, and possessive pronoun.